Temperature as a risk factor for outbreaks of Amoebic Gill Disease in farmed Atlantic salmon (Salmo salar) - Douglas-Helders, GM; Saksida, S; Raverty, S; Barbara Nowak (2001)
Amoebic Gill Disease (AGD) outbreaks in Atlantic salmon have recently occurred below the lower temperature limit previously recognised for Neoparamoeba pemaquidensis. This observation challenges the role of ambient water temperature as one of the prime risk factors for AGD.